AKTIVITAS HIPNOTIK KOMBINASI EKSTRAK ETANOL KANGKUNG AIR (IPOMOEA AQUATICA FORSSK.) âPEGAGAN (CENTELLA ASIATICA (L.) URB.) âPALA (MYRISTICA FRAGRANS HOUTT.) PADA MENCIT BETINA GALUR SWISS WEBSTER - Kaaffah, Silmi
Insomnia is a sleep disorder which daytime fatigue is present. People with insomnia tend to have trouble in concentrating and to do their job, making their productivity to decrease. Patient with insomnia are frequently treated by sedative-hypnotic drugs. Nevertheless, the use of synthetic drugs has side effects and people can develop tolerance to it. Therefore natural medicine can be used as an alternative. Traditionally, Nutmeg is used to give calming effect and induced sleep or drowsiness. The aim of this study is to determine hypnotic effect from Nutmeg extract, and its effect when combined with Water Spinach and Gotu Kola that have been proven to give sedative hypnotics effect. Water Spinach extract, Gotu Kola extract and Nutmeg extract were obtained by maceration with ethanol. The study used female mice (Swiss Webster) divided into 16 groups. The groups consist of vehicle (CMC-Na 0,5%), reference drugs (diazepam 3 mg/kg BW), ethanol extract of Nutmeg at 25, 50, 100, and 200 mg/kg BW, combination extract, ethanol extract of Water Spinach and Gotu Kola at 100 mg/kg BW. The hypnotic effect test was done by injecting ketamine 150 mg/kg (i.p) to induce sleep, and then sleep latency, duration, efficiency and sleep cycle in mice were measured. Data obtained were analyzed statistically using One Way Anova-Post Hoc (LSD). The result showed that there was no significant difference in sleep efficiency between ethanol extract of Nutmeg at a dose of 25 mg/kg BW (94.95 ± 1.83 %) with diazepam group (94.27 ± 0.79 %) and the extract could increase sleep efficiency significantly compared to vehicle group (89.68 ± 1.50 %). Ethanol extract of Nutmeg were then combined with ethanol extract of Water Spinach and Gotu Kola in different ratio. The results showed that combination of ethanol extract of Gotu Kola at a dose of 25 mg/kg BW + Nutmeg at a dose of 50 mg/kg BW + Water Spinach at a dose of 25 mg/kg BW had synergistic activity compared to individual extract in reducing sleep latency. The combination also increased sleep efficiency (95.27 ± 0.74 %) significantly compared to vehicle group (85.91 ± 1.04 %) and showed no significant difference compared to diazepam group (94.01 ± 0.36 %).